2019
DOI: 10.26773/smj.190209
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physical Therapy in Patients with Chronic Low Back Pain

Abstract: Low back pain is the most common cause of disability. Epidemiological studies have generally considered that risk factors for starting backache are interrelated in three dimensions: individual factors and lifestyle, physical or biomechanical factors, and psychosocial factors. The main aim of this study was to evaluate the effi cacy of physical therapy in patients with chronic non-specifi c low back pain. This retrospective study was conducted at the Diagnostic Therapeutic Center Rezonanca, Department of Physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Gashi, & Azemi, [31] presented knowledge on the benefits of physiotherapy sessions of reducing the LBP intensity in patients after 10 treatment sessions (each session included electrical nerve stimulation -15-20 min, hot packs -15 min and transverse massage -15-20 min). Russian investigators reported that the expediency of course of electroneuromyostimulation in professional athletes with a herniated intervertebral disc (L4-L5-S1) in early postoperative period [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gashi, & Azemi, [31] presented knowledge on the benefits of physiotherapy sessions of reducing the LBP intensity in patients after 10 treatment sessions (each session included electrical nerve stimulation -15-20 min, hot packs -15 min and transverse massage -15-20 min). Russian investigators reported that the expediency of course of electroneuromyostimulation in professional athletes with a herniated intervertebral disc (L4-L5-S1) in early postoperative period [13].…”
Section: Discussionmentioning
confidence: 99%
“…Also, physicians reported that combination of early postoperative stimulation (electroneuromyostimulation) and restriction of motor activity for 2 months with a subsequent transition to physical therapy is optimal for patients with operative treatment of lumbar spine [30]. Physicians reported on the high efficiency of the course of electroneuromyostimulation therapy for patients with back pain, including LBP and LDH [13,15,29,31]. In particular, Russian investigators reported a positive effect of 8 weeks of electroneuromyostimulation therapy on the symptoms of pain in professional athletes, who practiced various combat sports and plays, and returned to sport after endoprosthesis surgery [13].…”
Section: Methodsmentioning
confidence: 99%